Manufacturing Advantage: Why High-Performance Work Systems Pay OffManufacturing Advantage: Why High-Performance Work Systems Pay Off, by AppelbaumEileen BaileyThomas BergPeter, and KallebergArne L.. Ithaca, NY: Cornell University Press, 2000. - Harrell-Cook, Gloria (Academy of Management Review, 2001)
The article reviews the book ?Manufacturing Advantage: Why High-Performance Work Systems Pay Off,? by Eileen Appelbaum, Thomas Bailey, Peter Berg, and Arne L. Kalleberg.